FAKTOR PENYEBAB KETIDAAKURATAN SENSUS HARIAN PASIEN RAWAT INAP DI RUMAH SAKIT JIWA GRHASIA DIY - , SAGITA ARDIANTO NUGROHO, Eddy Kristiyono., A.Md.,Perkes., SKM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Data collection in the hospital daily census is the data that should be collected every day. The data is useful for monitoring the patient care every day, week, month. Furthermore, the data contained in the daily census will be processed in a recapitulation and will result in reporting. Census is useful to know the number of incoming patients, out patients, and the patient died. In addition to knowing the level of usage and calculate bed facility providing services kesehatan.Oleh therefore daily census of inpatients should be made as accurately as possible to support the hospitals reporting a careful, precise, and accurate. Objective: The general objective of this study was to determine the factors that cause inaccuracies daily census of inpatients in mental hospital Grhasia DIY. The specific objective of this study was to determine the process of making daily census of inpatients in the ward and to analyze the causes of inaccuracies daily census of inpatients. Methods: This study used a descriptive method with qualitative approach. The subjects in this study were part of the medical record reporting officer, chief medical records and ward nurses. Ni is the study of objects in daily census of inpatients. Results: Implementation daily census of inpatients is still running it manually and are under the process of changing to electronic. The process of making daily inpatient census carried out at night by the ward clerk, then decision made by the installation of officers at the medical records of the morning. In practice still found inaccuracies in the daily census of inpatients. There are several factors that lead to inaccuracies in the implementation of the daily census of inpatients. These factors, among others, human resources and coordination between medical records clerk with the ward officer.